Quality Parameters of Electricity Supplied to Electric Railways - Juraj Altus; Milan Novak; Alena Otcenasova; Michal Pokorny; Adam Szelag (Communications - Scientific letters of the University of Zilina, 2001)
The paper analyses the most relevant unfavourable impact of AC electric traction on the quality parameters of supplied electric energy. These are: power factor of fundamental harmonic and power factor, voltage a current harmonic components, unbalance and power factors in asymmetrically loaded lines and flicker. To confirm some propositions, the paper presents results of measurements in traction transformer substation ŽSR Nové Zámky. Also, the possibilities of unfavourableimpact elimination using filtering and compensating substation and power active filters are mentioned.